1995
DOI: 10.1074/jbc.270.9.4325
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis and Lysosomal Targeting of Epidermal Growth Factor Receptors Are Mediated by Distinct Sequences Independent of the Tyrosine Kinase Domain

Abstract: Ligand-induced internalization of the epidermal growth factor receptor (EGFR) leads to accelerated receptor degradation. Two models have been proposed to explain this. In the first model, induced internalization expands the intracellular pool of receptors, leading to enhanced lysosomal targeting. The second model proposes that activation of intrinsic receptor kinase activity induces inward vesiculation of endosomes, thus interrupting receptor recycling. To test these models, we created EGFR mutants that lack t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
125
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(128 citation statements)
references
References 62 publications
3
125
0
Order By: Relevance
“…It has previously been suggested that EGF receptor degradation is initiated by structural changes of the receptor that are stabilized by autophosphorylation and expose cryptic internalization and degradation sites (Opresko et al, 1995). Our results for the M-CSF receptor are largely consistent with this model except that autophosphorylation was not found to be critical, it may also not be critical for downregulation of the EGF receptor (Livneh et al, 1987).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…It has previously been suggested that EGF receptor degradation is initiated by structural changes of the receptor that are stabilized by autophosphorylation and expose cryptic internalization and degradation sites (Opresko et al, 1995). Our results for the M-CSF receptor are largely consistent with this model except that autophosphorylation was not found to be critical, it may also not be critical for downregulation of the EGF receptor (Livneh et al, 1987).…”
Section: Discussionsupporting
confidence: 87%
“…The binding of growth factors to receptors usually causes the internalization and degradation of the receptor-ligand complex, a process referred to as receptor downregulation (Opresko et al, 1995;Seaman et al, 1996). Receptor downregulation is important because it attenuates signalling, as shown by the ®nding that mutant receptors for EGF and PDGF that are resistant to ligand-induced degradation have ampli®ed mitogenic activity (Wells et al, 1990;Mori et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Endocytosis of the growth-factor receptors requires intrinsic tyrosine kinase activity [185,186]. Inactivation of the receptor kinase activity by a point mutation almost eliminates agonistinduced internalization of the epidermal-growth-factor receptor [187]. However, deletion of the entire tyrosine kinase domain, leaving the remaining C-terminal tail with its endocytic motifs intact, results in constitutive receptor endocytosis.…”
Section: Induction Of Agonist-induced Receptor Endocytosis : the Endomentioning
confidence: 99%
“…Thus exposure to agonists depletes the cell of surface receptors and accelerates receptor degradation, reflected by a 8-10-fold decrease in halflife [185]. The importance of the endogenous tyrosine kinase domain for endocytosis and trafficking of the epidermal growth factor receptor is controversial, and has been a topic of recent investigation [185,187,213]. The unoccupied epidermal growth factor receptor is internalized at a very low basal rate, and activation by agonist is necessary for rapid internalization and degradation.…”
Section: Lysosomal Targetingmentioning
confidence: 99%